Pelaksanaan Tera/Tera Ulang Oleh Metrologi Legal Dinas Perdagangan Dan Perindustrian Kota Gorontalo Sebagai Upaya Perlindungan Konsumen - Mohamad Arif Asiari; Fenty U. Puluhulawa; Julius T. Mandjo (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research aims to determine the implementation of tera/re-terra by the Legal Metrology Department of Trade and Industry of Gorontalo City as an effort to protect consumers. The type of research used in this research is empirical legal research which is intended to obtain clarity and understanding of the problems in research based on existing facts. Data sources were obtained through interviews, observation and documentation. Then analyzed descriptively qualitatively. The results of the research show that the implementation of tera/retracing by the Legal Metrology Department of Trade and Industry of Gorontalo City is carried out by carrying out retracing/retracing of scales which are included in the legal metrology category which is authorized for trading by the Ministry of Trade, in accordance with international standards. All UTTPs must be stamped/recast once a year in accordance with legal metrology laws and regulations. This aims to ensure that the UTTP equipment used by business actors complies with statutory provisions, so that the measurement results, measurements and scales are as they should be so that they do not harm consumers.